(untitled) (Journal of the College of Education for Women, 2019)
The Almighty Allah has addressed His followers by advising them to follow the example of the prophet (PBUH). Allah says: (INDEED IN THE MESSENGER OF ALLAH YOU HAVE A GOOD EXAMPLE TO FOLLOW). So, He was a true and everlasting example for the people to follow and imitate in all aspects of life. Knowledge and learning, especially Qura’nic knowledge, are among the priorities. The present study is concerned with how to follow the Prophet example (PBUH) in the field of Qur’an reciting. It aims at showing His instructions on Qur’an reciting, and how He was followed by His Companions. The present study falls into an introduction and four sections. Section One deals with the commands given by Allah to follow His prophet. Second Two is concerned with the Prophet’s in receiving and trusting the Qur’an. Section Three is about His efforts Prophet to Qur’an reciting. Finally, Section Four presents certain samples of the Prophet’s Companions. As for the conclusion, It shows the most important results of the study, following the references.